2002
DOI: 10.1097/01.lab.0000038924.67707.75
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Somatic Androgen Receptor Gene Mutations in Patients with Hormone-Refractory Prostate Cancer

Abstract: SUMMARY:Progression to hormone-refractory growth of prostate cancer has been suggested to be mediated by androgen receptor (AR) gene alterations. We analyzed AR for mutations and amplifications in 21 locally recurrent prostate carcinomas treated with orchiectomy, estrogens, or a combination of orchiectomy and estramustine phosphate using fluorescence in situ hybridization, single-strand conformation polymorphism, and DNA sequence analyses. Amplification was observed in 4 of 16 (25%) and amino acid changing mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 47 publications
0
38
0
4
Order By: Relevance
“…29,30,[39][40][41] The type of treatment given was also shown to influence the kind of mutation seen. 42 Since reports have shown that mutations are present in 20-40% of the advanced PCAs before therapy, 30,31 it could be hypothesized that the mutations were not induced by therapy but were pre-existent. Therefore, certain clones that can grow in the absence or presence of very little androgens are selected for growth during androgen withdrawal and grow aggressively to reestablish the disease.…”
Section: Amplification Of the Armentioning
confidence: 99%
“…29,30,[39][40][41] The type of treatment given was also shown to influence the kind of mutation seen. 42 Since reports have shown that mutations are present in 20-40% of the advanced PCAs before therapy, 30,31 it could be hypothesized that the mutations were not induced by therapy but were pre-existent. Therefore, certain clones that can grow in the absence or presence of very little androgens are selected for growth during androgen withdrawal and grow aggressively to reestablish the disease.…”
Section: Amplification Of the Armentioning
confidence: 99%
“…4,9 Much of our understanding of AR function is derived from the study of somatic missense mutations in the AR gene in patients with androgen insensitivity syndrome (inactivating mutations) or in primary, recurrent and metastatic prostate tumors and cell lines. [10][11][12] AR variants identified in clinical prostate tumors typically exhibit promiscuous activation by nonandrogenic ligands and/or enhanced transactivation capacity due to altered interactions with coregulators. 13 The prototypical example of AR promiscuity is AR-T877A (T857A in mice), a variant expressed in the LNCaP prostate cancer cell line that is activated by estrogen, progesterone and the AR antagonist, hydroxyflutamide, in addition to androgens.…”
mentioning
confidence: 99%
“…9,10 Thus AR can be active even in low androgen environment. AR mutations cluster in an area that defines AR protein interactions, [11][12][13] they are rare in local disease [14][15][16] but frequent in metastases where they enable binding with estradiols, glucocorticoids and anti-androgens 11,17 (reviewed in Ref. 17).…”
mentioning
confidence: 99%